Management of COVID-19-related post-intubation tracheal stenosis - Conforti, Serena; Licchetta, Gloria; Reda, Marco; Astaneh, Arash; Pogliani, Luca; Fieschi, Stefano; Rinaldo, Alessandro; Torre, Massimo (Frontiers in Surgery, 2023)
Introduction The Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) pandemic has affected Italy since the beginning of 2020. Endotracheal intubation, prolonged mechanical ventilation, and tracheostomy are frequently required in patients with severe COVID-19. Tracheal stenosis is a potentially severe condition that can occur as a complication after intubation. The aim of this study was to evaluate the utility and safety of endoscopic and surgical techniques in the treatment of tracheal stenosis related to COVID-19. Materials and Methods Between June 2020 and May 2022, consecutive patients with tracheal stenosis who were admitted to our surgical department were considered eligible for participation in the study. Results A total of 13 patients were included in the study. They consisted of nine women (69%) and four men (31%) with a median age of 57.2 years. We included seven patients with post-tracheostomy tracheal stenosis. Bronchoscopy was performed to identify the type, location, and severity of the stenosis. All patients underwent bronchoscopic dilation and surveillance bronchoscopy at 7 and 30 days after the procedure. We repeated endoscopic treatment in eight patients. Three patients underwent tracheal resection anastomosis. Final follow-up bronchoscopy demonstrated no residual stenosis. Conclusions The incidence of and risk factors associated with tracheal stenosis in critically ill patients with COVID-19 are currently unknown. Our experience confirms the efficacy and safety of endoscopic management followed by surgical procedures in cases of relapsed tracheal stenosis.